2013
DOI: 10.1371/journal.pone.0075965
|View full text |Cite
|
Sign up to set email alerts
|

JNK and Macroautophagy Activation by Bortezomib Has a Pro-Survival Effect in Primary Effusion Lymphoma Cells

Abstract: Understanding the mechanisms of autophagy induction and its role during chemotherapeutic treatments is of fundamental importance in order to manipulate it to improve the outcome of chemotherapy. In particular whether the bortezomib-induced autophagy plays a pro-survival or pro-death role is still controversial. In this study we investigated if bortezomib induced endoplasmic reticulum (ER) stress and activated autophagy in Primary Effusion Lymphoma (PEL) cells and how they influenced cell survival. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 42 publications
(54 reference statements)
3
54
0
Order By: Relevance
“…29,30 However, the molecular mechanism by which JNK suppresses apoptosis is incompletely understood. Recently, several researchers have demonstrated that JNK is required for the cell survival via induction of autophagy, [31][32][33] consistent with our present work. Our data also suggested that JNK activated ERK1/2 MAPK when HPEKs were irradiated with UVB, because phosphorylation of ERK1/2 was partially decreased by a JNK inhibitor (Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…29,30 However, the molecular mechanism by which JNK suppresses apoptosis is incompletely understood. Recently, several researchers have demonstrated that JNK is required for the cell survival via induction of autophagy, [31][32][33] consistent with our present work. Our data also suggested that JNK activated ERK1/2 MAPK when HPEKs were irradiated with UVB, because phosphorylation of ERK1/2 was partially decreased by a JNK inhibitor (Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…We show for the first time an interplay between STAT3 and HSF1 in PEL cells, even if a cross-talk between STAT family members and HSF1 has been reported in other cell types [12,13]. More importantly, in this study, we found that, due to the reduction of HSF1 and HSP response, AG490 triggered a complete autophagy, aimed at the elimination of the accumulating unfolded proteins [30] which is a rapidly occurring event in cancer cells characterized by an elevated level of protein synthesis, such as PEL cells [18]. Indeed we found that autophagy induction was a pro-survival mechanism and that autophagy inhibitors further increased the AG490 cytotoxic effect against PEL cells.…”
Section: Discussionmentioning
confidence: 62%
“…Here we found that STAT3 inhibition by AG490 down-regulated HSF1 together with Heat Shock Protein 70 (HSP70), chaperone essential for PEL cell survival [3,16]. Cancer cells, in their basal stressful conditions and even more during heat shock or chemotherapies, up-regulate HSPs in order to assure the correct protein folding [3,[17][18][19]. A similar role, in protecting cells from basal or induced stressful conditions, is also played by autophagy, a catabolic pathway that leads to the lysosomal clearance of unfolded proteins and other unwanted cellular materials [20].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we previously demonstrated that ER stress was induced in a time-dependent manner in PEL cells undergoing bortezomib treatment. In this study, we investigated whether ER stress would occur concomitantly with viral replication and autophagy induction both in KSHV and as EBV-positive lymphoma cells treated with bortezomib 13 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of ER stress induced by bortezomib, c-Jun N-terminal Protein Kinase (JNK) can be activated by the IRE1 arm of UPR and may promote autophagy by phosphorylating Bcl-2 12 . Accordingly, we have previously shown that bortezomib-induced ER stress promoted a pro-survival autophagy through the activation of JNK in PEL cells 13 . Autophagy is a catabolic process that usually helps cancer cells to survive in stressful conditions such as during starvation or in the course of chemotherapies.…”
Section: Introductionmentioning
confidence: 94%